Integrating Arabic Language Pedagogy and Prayer Supplications: Enhancing Khushūʿ through Linguistic Comprehension - Segaf Baharun; Moh. Tohiri Habib; Nurin Sakinah (Attanwir : Jurnal Keislaman dan Pendidikan, 2026)
Arabic has long been recognized as the primary language through which Islamic teachings are conveyed, making it essential for understanding religious texts and devotional practices. In many Islamic educational contexts, however, students often memorize prayer supplications without fully comprehending their linguistic meanings. This gap between recitation and comprehension may limit the development of spiritual concentration (khushūʿ) during prayer. This study explores how Arabic language pedagogy can be integrated with prayer supplications to enhance students’ linguistic understanding and reflective engagement during worship. This research employed a qualitative design conducted at Pondok Pesantren Darullughah Wadda’wah, involving 30 first-grade Tsanawiyah students who regularly participate in Arabic language learning and congregational prayers. Data were collected through classroom observations, semi-structured interviews, and document analysis of instructional materials related to prayer recitations. The collected data were analyzed using the qualitative framework of data reduction, data display, and conclusion drawing. Triangulation was applied to ensure the credibility of the findings. The results reveal that integrating prayer supplications into Arabic language instruction allows students to engage with authentic linguistic materials that are directly connected to their daily religious practices. Teachers explained the lexical meanings, grammatical structures, and contextual significance of selected supplications, enabling students to link linguistic knowledge with spiritual reflection. Interview findings further indicate that students who understand the meanings of the supplications tend to demonstrate greater attentiveness and reflective awareness during prayer. Rather than reciting mechanically, they perceive prayer as meaningful communication with God. The study concludes that integrating Arabic language pedagogy with prayer supplications can simultaneously strengthen linguistic competence and spiritual awareness among students. This approach offers a pedagogical model that bridges Arabic language learning with Islamic devotional practice, particularly in pesantren contexts where language education and religious life are closely intertwined. Keyword : Arabic pedagogy, prayer supplications, linguistic comprehension, spiritual concentration, pesantren education